Entrepreneurship-Based Multicultural Education: Fostering Batak Toba Cultural Awareness and Entrepreneurial Creativity in Jagung Kindergarten Children, Tampahan District - Sitompul, Rosalinda Septiani; Manurung, Herta; Tambunan, Bonari Hasudungan Rusmanto; Rajagukguk, Holmes; Siregar, Christyani; Togatorop, Fretty Elisabet; Pasaribu, Junjungan (Unram Journal of Community Service, 2025)
The development of the digital era has brought significant changes to children's education patterns, which not only emphasizes cognitive aspects but also demands the development of life skills, including an entrepreneurial spirit. Entrepreneurship from an early age is seen as an important strategy for instilling independence, creativity, innovation, and the courage to take risks. Integrating art, particularly traditional Batak Toba music, with entrepreneurship education offers a relevant approach to shaping a generation that is creative, productive, and rooted in local culture. However, several key issues still exist, such as children's low awareness of the economic value of artwork, minimal use of simple technology in art education, and a lack of innovation in art products aimed at business opportunities. To address these challenges, the service team from Sisingamangaraja XII University of Tapanuli implemented the program "Entrepreneurship-Based Multicultural Education: Fostering Batak Toba Cultural Awareness and Entrepreneurial Creativity in Early Childhood Education Children in Jagung Village, Tampahan District" in Gurgur Aek Raja Village, Tampahan District, Toba Regency. The participants in the activity included 32 preschool children, 2 teachers, parents, traditional music trainers, and the community service team. The implementation method is designed in five main stages: (1) socialization about the importance of art entrepreneurship from an early age; (2) introductory and practical training on traditional Batak Toba musical instruments (hasapi, sulim, taganing, garantung, sordam); (3) application of simple technology thru the creation of musical instruments from local materials; (4) continuous mentoring and evaluation; and (5) program sustainability planning thru integration into the early childhood education curriculum. The results of the activities show a positive response from all parties. The children looked enthusiastic, more confident, and were able to play simple rhythmic patterns. Teachers gained new skills to integrate traditional music into learning, while parents increasingly supported children practicing at home. The handover of a set of traditional musical instruments strengthens the sustainability of the program. Additionally, the activities resulted in innovations in the form of hard technology (modified traditional musical instruments and simple musical instruments made from local materials) and soft technology (local culture-based learning methods, musical skills, and knowledge of art entrepreneurship). The evaluation shows an improvement in understanding of Batak Toba culture, musical skills, creativity, and early indications of an entrepreneurial spirit in children. The real impact of this program can be seen in three main dimensions: (1) education, namely the development of children's creativity, courage, and skills; (2) socio-cultural, namely the growth of awareness and pride in preserving Batak Toba culture; and (3) economic, namely the emergence of business opportunities based on traditional art and music. The external activities include scientific articles, mass media publications, documentary videos, and educational posters.